The Use of Digital Twins to Address Smart Tourist Destinations’ Future Challenges - Lázaro Florido-Benítez (Platforms)
This research aims to conceptualise the use of the digital twins (DT) tool in tourism to address smart tourist destinations’ future challenges to enhance tourists’ experiences and residents’ quality of life through better services developed by DTs. This paper investigated the use of DT technology to tackle the new challenges facing smart tourist destinations (STDs) in terms of urban planning, sustainability, security, marketing, and tourism activities by using data on this topic from expert researchers and public and private organisations. Also, this research adopted a systematic review approach to analyse and illustrate the existing literature on the topic of DTs and their use for STDs, which helped us develop the DT concept in a STD context. The findings of this research reveal that DT technology is emerging as a disruptive technology tool that is being used to improve the management of STDs in terms of their efficiency, safety, sustainability, environmental protection, productivity, and energy consumption. Moreover, DT technology is a nascent tool in the tourism and marketing industries, but its versatility in relation to its capacity to analyse data and predict the behaviour of tourism and business ecosystems to address relevant issues at STDs gives it a key role in the tourism industry. Finally, a new definition of DT technology has been included in this study within a tourism and STDs context, filling the gap in this topic in the tourism industry according to some researchers’ suggestions. There are limited scientific publications about DT technology that jointly tackle the DT technology and STDs sphere. Accordingly, this manuscript defines DT technology and provides a new viewpoint of this technology that will help to initiate academic discussions on DT tourism within the context of STDs.